(untitled) - Beer, Lawrence W. (Boulder, 2002)
This book is a splendid introduction to the Constitution of Japan and its relevance not only for the daily life of the Japanese but also for fundamental human rights and world order. It is very readable and highly recommended for college students, general readers, and specialists.
Keywords: Japan, Kenpo,Constitutional history,Japan; Politics and government; 20th century; Japan